The Wiley Blackwell handbook of the psychology of recruitment, selection and employee retention - Goldstein, Harold, 1965-; Pulakos, Elaine Diane; Passmore, Jonathan; Semedo, Carla, 1973- (Wiley-Blackwell handbooks in organizational psychology., 2017)
This handbook makes a unique contribution to the fields of organizational psychology and human resource management by providing comprehensive coverage of the contemporary field of employee recruitment, selection and retention. It provides critical reviews of key topics such as job analysis, technology and social media in recruitment, diversity, assessment methods and talent management, drawing on the work of leading thinkers including Melinda Blackman, Nancy Tippins, Adrian Furnham and Binna Kandola. The contributors are drawn from diverse backgrounds and a wide range of countries, giving the volume a truly international feel and perspective. Together, they share important new work which is being undertaken around the globe but is not always easily accessible to real-world practitioners and students.